Two new species, and additional records, of aphelinids from Egypt (Hymenoptera: Aphelinidae) - Evans, Gregory A.; Abd-Rabou, Shaaban (Zootaxa, 2005)
Two new species of aphelinids, Pteroptrix aegyptica and Encarsia perconfusa, are described and illustrated from Egypt from Parlatoria blanchardi and Tetraleurodes leguminicola, respectively. Several collection records are given for aphelinids reared from known hosts in Egypt.